Knockdown of Nucleosome Assembly Protein 1‐Like 1 Induces Mesoderm Formation and Cardiomyogenesis Via Notch Signaling in Murine‐Induced Pluripotent Stem Cells. (17th June 2014) - Gong, Hui; Yan, Yuan; Fang, Bo; Xue, Yuanyuan; Yin, Peipei; Li, Lu; Zhang, Guoping; Sun, Xia; Chen, Zhidan; Ma, Hong; Yang, Chunjie; Ding, Yingjiong; et al.
Abstract : Low efficiency of cardiomyocyte differentiation from induced pluripotent stem cells (iPSCs) hinders the clinical application of iPSC technology for cardiac repair strategy. Recently, we screened out nucleosome assembly protein 1‐like 1 (Nap1l1), which was downregulated during the differentiation of P19CL6 cells into cardiomyocytes. Here, we attempted to study the role of Nap1l1 in cardiomyogenesis of iPSC. Nap1l1 was downregulated during the differentiation of iPSC. Knockdown of Nap1l1 dramatically enhanced the differentiation of iPSC into functional cardiomyocytes while overexpression of Nap1l1 sharply lowered the differentiation. Moreover, although Nap1l1‐knockdown had little effect on endoderm differentiation, the Nap1l1 modulation significantly accelerated mesoderm development. Re‐expressing Nap1l1 in Nap1l1‐knockdown‐iPSC rescued the effects of Nap1l1. Inducibly overexpressing Nap1l1 at early stage of differentiation greatly inhibited mesoderm induction and cardiogenesis of iPSC. However, mesoderm stem cells (Flk‐1‐positive cells) originated from Nap1l1‐knockdown‐ or ‐overexpression‐iPSC showed no difference in further cardiomyocyte differentiation compared with that of control‐iPSC. Further study revealed that Nap1l1‐overexpression increased γ‐secretase activity and the expression of Notch intracellular domain (NICD) and downstream genes during the differentiation of iPSC. γ‐Secretase inhibitor DAPT (N‐[N‐(3, 5‐difluorophenacetyl)‐L‐alanyl]‐S‐phenylglycinet‐butyl ester) greatly suppressed the production of NICD and abolished the inhibitory effects of Nap1l1‐overexpression on mesoderm induction and cardiogenesis. These findings demonstrate that downregulation of Nap1l1 significantly enhances mesodermal induction and subsequent cardiogenesis of murine iPSC via inhibition of γ‐secretase‐regulated Notch signaling, which would facilitate the application of iPSC in heart diseases. Stem Cells   2014;32:1759–1773